Mesenchymal stem cells in infantile haemangioma. Issue 3 (17th January 2011) - Itinteang, Tinte; Vishvanath, Anasuya; Day, Darren J; Tan, Swee T
Abstract : Background: Fibro-fatty deposition commonly occurs during involution of infantile haemangioma (IH). Mesenchymal stem cells have been identified in this tumour and have been proposed to be recruited from the bone marrow and/or adjacent niches, and then give rise to the fibro-fatty tissue. The authors have recently demonstrated that the capillary endothelium of proliferating IH co-expresses primitive mesodermal, mesenchymal and neural crest markers and proposed that this same endothelium has the ability to give rise to cells of mesenchymal lineage that constitute the fibro-fatty deposition. Methods: Immunohistochemistry and real-time RT-PCR were used to further characterise proliferating IHs and haemangioma explant-derived cells (HaemEDCs). Results: The authors have further confirmed expression of the mesenchymal-associated proteins including preadipocyte factor-1, a mesenchymal differentiation inhibition-associated cytokine. The HaemEDCs could be differentiated into osteoblasts and adipocytes, indicating their functional potential for terminal differentiation. Discussion: The collective expression of neural crest, mesenchymal and mesenchymal differentiation inhibition-associated proteins on the endothelium of proliferating IH suggests that the cells in the capillary endothelium within the lesion possess the ability to undergo terminal mesenchymal differentiation during the proliferating phase, but are inhibited from doing so.